"Engineering Resilience" Into Split-Second Shoot/No Shoot Decisions: The Effect of Muzzle-Position. (June 2021) - Taylor, Paul L.
The purpose of this study was to explore the feasibility of engineering resilience into the split-second decision environment police officers face during potential deadly force encounters. Using a randomized controlled experiment that incorporated a police firearms training simulator and 313 active law enforcement officers, this study examined the effects of muzzle-position – where an officer points their weapon – on both officer response time to legitimate threats and the likelihood for misdiagnosis shooting errors when no threat was present. The results demonstrate that officers can significantly improve shoot/no-shoot decision-making without sacrificing a significant amount of time by taking a lower muzzle-position when they are dealing with an ambiguously armed person – a person whose hands are not visible.